The role of the Diosdado Macapagal International Airport in the development of Clark as a global gateway - Gonzales, Katrina; Manabat, Archie; Salas, Jathniel Joseph; Sitchon, Jeffrey Ron; Sitchon, Katrina
Included in President Gloria Macapagal-Arroyo's 10-point agenda is the development of Clark and Subic as the best international service and logistic centers in the region. This study focuses on the significance of Diosdado Macapagal International Airport in the fulfillment of Clark Special Economic Zone as a global gateway. The study presents evidences that the presence of DMIA in CSEZ affect the location decision of investors as it will be significant for the present and future use. It was also found out that DMIA plays a big part in promoting logistic activities in CSEZ. The study also aims to identify the key areas of improvement for the airport's facilities and services to boost its full development to become the country's premier gateway. The analysis shows that the Diosdado Macapagal International Airport is playing a vital role in the fulfillment of the Global Gateway Program.